OP0098 A Pattern of Toll-Like Receptor Activation Characterizes Lupus Patients with Antibodies to Ribonucleoprotein Complexes. (10th June 2014) - Pérez-Ferro, M.; Romero-Bueno, F.I.; Serrano del Castillo, C.; Franco, C.; Martínez-Lόpez, J.A.; de la Hera, F.J.; Herrero-Beaumont, G.; Sanchez-Pernaute, O.
Abstract : Background: Systemic lupus is a highly heterogeneous disease. Along with production of autoantibodies against double stranded DNA, some patients also show reactivity for different ribonucleoprotein complexes (RNP), and they appear to share a distinct phenotype. Toll-like receptors (TLR) are pathogen detectors that trigger the innate defense and lead to the maturation of immunocompetent cells. Endosomal TLR have been associated to the pathogenesis of SLE and to the production of autoantibodies. We have recently shown that also surface TLR were associated to more active disease in a cohort of lupus patients. Objectives: Our current objective was to seek for a specific innate activation footprint in circulating mononuclear cells (PBMC) from the anti RNP+ subgroup of lupus patients. Methods: Thirty six patients diagnosed with lupus and 13 matched controls were recruited. Cumulative features and biologic markers were registered. PBMC were isolated and the CD14, CD3, and CD19 subpopulations were positively selected with magnetic sorting. The mRNA levels of TLR, interferon inducible peptide 10 (IP10), the MHC class I-related ligand A (MICA), and the expression of miR146a, and miR181a were determined with qPCR techniques. Statistics were carried out with Spearman's correlation, Mann-Whitney and Kruskal-Wallis tests for independent samples. Categorical variables were compared with Chi-Square and Fisher's exact test. Significance was set at 95%. Results: Anti RNP antibodies were found in 55% of the patients. Of all the TLR studied in the sorted subpopulations of PBMC, gene expression levels of TLR2, TLR4 and TLR7 in CD14 cells were significantly higher in the anti RNP+ subgroup of patients (p 0.008, p 0.007, p 0.01, respectively). The 3 molecules were significantly enhanced in active disease, but were not associated to low complement or higher ANA titers. There was a strong correlation between the up-regulation of all TLR in CD14 cells and the gene expression levels of IP10 in these cells (p<0.001), as well as in CD19 cells (p<0.05). The induction of these TLR was also correlated with the gene expression of MICA in CD14 and CD3 cells. In contrast, levels of miR146a, a regulator of the innate activation of nuclear factor kappa B, were not changed upon TLR induction, while levels of miR181a in CD3 cells were negatively correlated with MICA expression levels in these cells and with levels of TLR7 in CD14 cells. An increase in IP10 levels in CD14 and in CD3 cells was found in anti RNP+ patients compared to healthy controls. Compared to the anti RNP- subgroup, anti RNP+ patients showed an up-regulation of IP10 in CD14+ cells, and of MICA in both CD14 and CD3 cells, while the RNP- subgroup showed a profound down-regulation of MICA in CD3 compared to healthy controls. Conclusions: Our results identified an innate activation pathway selectively associated to the subgroup of anti RNP+ lupus patients. Our data showed relevant differences in the phenotype of monocytes and T lymphocytes exhibited by anti RNP+ and RNP- patients, and these findings suggest that different pathogenic factors trigger an IFN response in both subgroups as well. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5350